Direct and indirect calorimetry of lactate oxidation: implications for whole-body energy expenditure - Scott, C. B.; Kemp, R. B. (Journal of Sports Sciences, 2005)
Whole-body energy expenditure for heavy/severe exercise is currently accounted for by either: (1) anaerobic and oxygen uptake measures during exercise where recovery energy expenditure is omitted; or (2) oxygen uptake during, and an EPOC (excess post-exercise oxygen consumption), measure following exercise where substrate level phosphorylation during exercise is considered part of EPOC. Simultaneous direct/indirect calorimetry enabled us to determine if a thermodynamic reversal (i.e. heat consumption) takes place as the highly exothermic pyruvate to lactate reaction proceeds in the opposite direction. Reversibility implies that oxygen uptake (e.g. EPOC) can indeed account for rapid glycolytic ATP production regardless if lactate is formed or not (e.g. 1.2 g glucose catabolism = 20.9 kJ · l O2 - 1). Cultured hybrid cells and mouse cardiac muscle fibres were utilized in simultaneous calorimetry and respirometry experiments where pyruvate or lactate was predominantly oxidized. The calorimetric to respiratory ratio was determined using heat flux (pW · cell - 1) and oxygen flux (pmol · s - 1 · cell - 1) measures. Ten cell experiments gave calorimetric to respiratory ratios that showed no statistical difference (P = 0.97) whether cells respired predominantly on lactate (-516 ± 53 kJ · mol O2 - 1) or pyruvate (-517 ± 89 kJ · mol O2 - 1). In three cardiac preparations, the calorimetric to respiratory ratio was - 502 ± 15 kJ · mol O2 - 1 for lactate and - 506 ± 47 kJ · mol O2 - 1 for pyruvate, again a non-significant difference (P = 0.91). Heat consumption did not occur during lactate oxidation. These results suggest that rapid glycolytic ATP and lactate production, and lactate oxidation, are both independently associated with heat production and thus represent separate and additive components to the measurement of total energy expenditure for exercise and recovery.